2016
DOI: 10.1515/acve-2016-0015
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Pre-Mortem Conditions on Pale, Soft and Exudative (PSE) and Dark, Firm and Dry (DFD) Pork Meat

Abstract: The aim of this study was to determine the effect of gender, stocking density in the transport vehicle, lairage time and season on the incidence of skin lesions on pig carcasses and PSE and DFD meat. Skin lesions on carcasses (480, in total) were assessed according to the Welfare Quality® protocol (2009). The pH and temperature measurements were performed 45 minutes after slaughter. The group of carcasses with skin lesions score 2 had signifi cantly higher incidence of PSE and DFD meat compared to the groups o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 26 publications
3
19
1
4
Order By: Relevance
“…Therefore, animals might benefit from additional insulation with appropriate bedding in the transporter and holding pens, which would protect them from cold stress, and ensure thermal comfort (Goumon et al, 2013). In the present research, the pigs slaughtered in summer had the lowest pH 45 value and the highest incidence of PSE meat (P <0.05) (Table 3), as observed by other researchers (Guàrdia et al, 2004, Correa et al, 2013, Čobanović et al, 2016. Because pigs do not have functional sweat glands, they have limited capacity to dissipate body heat rapidly enough and are sensitive to warm ambient conditions (Guàrdia et al, 2004).…”
Section: Resultssupporting
confidence: 83%
“…Therefore, animals might benefit from additional insulation with appropriate bedding in the transporter and holding pens, which would protect them from cold stress, and ensure thermal comfort (Goumon et al, 2013). In the present research, the pigs slaughtered in summer had the lowest pH 45 value and the highest incidence of PSE meat (P <0.05) (Table 3), as observed by other researchers (Guàrdia et al, 2004, Correa et al, 2013, Čobanović et al, 2016. Because pigs do not have functional sweat glands, they have limited capacity to dissipate body heat rapidly enough and are sensitive to warm ambient conditions (Guàrdia et al, 2004).…”
Section: Resultssupporting
confidence: 83%
“…This also applied if the transport route runs through heavy traffic areas or urban zones where ventilation may decrease due to lower speeds [45]. Studies by Cobanovic et al [46] found that reduced space (<0.3 m 2 /100 kg pig) during transport increased indices of lesions, final pH values, and the incidence of DFD meat. However, the same study [46] demonstrated that when more space is available (above 0.5 m 2 /100 kg), pigs can move around more freely inside the vehicle, resulting in an increased frequency of cutaneous lesions, which can serve as an important tool for predicting defects in meat quality since higher incidences of such injuries have been associated with higher percentages of PSE meat [46].…”
Section: Loading Densitymentioning
confidence: 99%
“…The day of slaughter has been identified as one of the most stressful stages in a pig's life, which negatively affects pig health, welfare, carcass characteristics, and meat quality [1][2][3][4][5]. This is because pigs are inevitably exposed to handling, loading, transportation, unloading, adverse weather conditions, mixing with unfamiliar animals, and physical and emotional stress owing to the new accommodation [6].…”
Section: Introductionmentioning
confidence: 99%